Decellularized human colorectal cancer matrices polarize macrophages towards an anti-inflammatory phenotype promoting cancer cell invasion via CCL18. (April 2017) - Pinto, M.L.; Rios, E.; Silva, A.C.; Neves, S.C.; Caires, H.R.; Pinto, A.T.; Durães, C.; Carvalho, F.A.; Cardoso, A.P.; Santos, N.C.; Barrias, C.C.; Nascimento, D.S.; et al.
Abstract: Macrophages are frequently identified in solid tumors, playing important roles in cancer progression. Their remarkable plasticity makes them very sensitive to environmental factors, including the extracellular matrix (ECM). In the present work, we investigated the impact of human colorectal tumor matrices on macrophage polarization and on macrophage-mediated cancer cell invasion. Accordingly, we developed an innovative 3D-organotypic model, based on the decellularization of normal and tumor tissues derived from colorectal cancer patients' surgical resections. Extensive characterization of these scaffolds revealed that DNA and other cell constituents were efficiently removed, while native tissue characteristics, namely major ECM components, architecture and mechanical properties, were preserved. Notably, normal and tumor decellularized matrices distinctly promoted macrophage polarization, with macrophages in tumor matrices differentiating towards an anti-inflammatory M2-like phenotype (higher IL-10, TGF-β and CCL18 and lower CCR7 and TNF expression). Matrigel invasion assays revealed that tumor ECM-educated macrophages efficiently stimulated cancer cell invasion through a mechanism involving CCL18. Notably, the high expression of this chemokine at the invasive front of human colorectal tumors correlated with advanced tumor staging. Our approach evidences that normal and tumor decellularized matrices constitute excellent scaffolds when trying to recreate complex microenvironments to understand basic mechanisms of disease or therapeutic resistance.